1982
DOI: 10.1111/j.1365-2621.1982.tb12886.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chloride Salts on Physical, Chemical and Sensory Properties of Frankfurters

Abstract: Triplicate 4.5 kg batches of frankfurters formulated with either pork/beef or mechanically deboned turkey (MDT) were made to replace all (100%) or part (35%) of the sodium chloride (NaCl) with either potassium chloride (KCl), magnesium chloride (MgClz) or lithium chloride (LiCl). Regardless of storage period or formulation, replacing all of the NaCl with either KC1 or MgCl, was detrimental to flavor. This same replacement with LiCl was not detrimental to flavor in pork/beef formulations. Data suggest that MgCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 12 publications
1
43
0
4
Order By: Relevance
“…The first approach consists in the partial or total substitution of NaCl by other chloride salts (potassium, calcium and magnesium chloride) or by non-chloride salts, such as phosphates or a combination of any of the above approaches (Sofos, 1986(Sofos, , 1989Terrell, 1983). Many studies on NaCl reduction or substitution have been performed on dry-fermented sausages and dry-cured ham (Gelabert et al, 2003;Gou et al, 1996;Hand et al, 1982;Ibáñez et al, 1996Ibáñez et al, , 1997Keeton, 1984;Ruusunen and Puolanne, 2005). However, no attempts have been done to study the salting kinetics of these products using different combinations of salts.…”
Section: Introductionmentioning
confidence: 98%
“…The first approach consists in the partial or total substitution of NaCl by other chloride salts (potassium, calcium and magnesium chloride) or by non-chloride salts, such as phosphates or a combination of any of the above approaches (Sofos, 1986(Sofos, , 1989Terrell, 1983). Many studies on NaCl reduction or substitution have been performed on dry-fermented sausages and dry-cured ham (Gelabert et al, 2003;Gou et al, 1996;Hand et al, 1982;Ibáñez et al, 1996Ibáñez et al, , 1997Keeton, 1984;Ruusunen and Puolanne, 2005). However, no attempts have been done to study the salting kinetics of these products using different combinations of salts.…”
Section: Introductionmentioning
confidence: 98%
“…There are many commercial mixtures, and they usually contain potassium chloride. Hand, Terrell and Smith (1982b) concluded that NaCl (2.8%) can be replaced with 35% KCl (by ionic basis) but not with MgCl 2 without detrimental effects on shrinkage. This can be expected due to the high salt levels, but technological difficulties might have been expected if the reference salt content would have been markedly lower.…”
Section: Cooked Sausagesmentioning
confidence: 99%
“…El empleo de sales divalentes, como CaCl 2 y MgCl 2, como sustitutos parciales del contenido de NaCl no está muy estudiado, y las pocas investigaciones que hay al respecto ponen de manifiesto que el uso de este tipo de sales genera defectos en la calidad final de los productos (Hand et al, 1982a;Gimeno et al, 1999). A pesar de ello, el empleo de estas mezclas de sales no solamente permite reducir el contenido de sodio en los productos cárnicos, sino que mejora la aportación nutricional diaria de este tipo de minerales (Gimeno, et al, 1998).…”
Section: Capítulo III Propiedades Bioquímicas Y Sensoriales En Lomos unclassified
“…Esto podría atribuirse al empleo de una adecuada concentración de KCl que juntamente con pequeñas cantidades de sales divalentes, evitó que se detectaran olores y sabores extraños (off-flavors) en el producto final. De hecho, varios autores (Hand et al, 1982a;Frye et al, 1986) observaron ésto cuando usaron MgCl 2 como agente de curado. Por consiguiente, el tratamiento II podría ser el elegido como la mejor opción para reducir el contenido de NaCl sin que se viera afectada la aceptabilidad del producto final.…”
Section: Capítulo III Propiedades Bioquímicas Y Sensoriales En Lomos unclassified
See 1 more Smart Citation